Financial aspect and healthcare outcomes: Lessons learned from COVID-19 - AlOmari, Firas; Bakar Abdul Hamid, Abu (Journal of Innovation in Business and Economics, 2023)
The main purpose of this review paper is to clarify the relationship between care cost, service quality, patient satisfaction, patient loyalty, and medication adherence. In addition, we tried to explore the impact of financial crisis on healthcare services.